(untitled) (JURNAL PENGMAS KESTRA (JPK), 2025)
Breast engorgement is a common problem experienced by postpartum mothers, particularly primigravida women, mainly due to ineffective breastfeeding practices, delayed milk flow, and limited knowledge and skills related to breast care. This condition can cause pain, discomfort, psychological distress, and may interfere with successful breastfeeding, including exclusive breastfeeding. Therefore, promotive and preventive efforts through comprehensive and sustainable education are essential. This community service activity aimed to improve postpartum mothers’ knowledge and skills in breast care as a preventive measure against breast engorgement and to support smooth breastfeeding. The activity was conducted using an educational and participatory approach involving 30 postpartum mothers in the working area of a primary healthcare facility. The implementation methods included health education using educational media, interactive discussions, as well as demonstrations and hands-on assistance in breast care practices. Evaluation was carried out through pretest and posttest assessments of knowledge and observation of breast care skills. The results showed a significant improvement in mothers’ knowledge, with the proportion of participants in the good knowledge category increasing from 30% before the intervention to 86.7% after the intervention. Breast care practice skills also increased markedly from 26.7% to 90%, while complaints of breast engorgement decreased from 60% to 16.7%. In conclusion, education and assistance in breast care are effective in improving postpartum mothers’ knowledge and skills and in reducing complaints of breast engorgement. This activity is recommended to be integrated sustainably into postpartum maternal health services to support breastfeeding success and improve the quality of maternal and infant health.